Renal Cell Carcinoma Associated with Mycosis Fungoides: A Paraneoplastic Syndrome. (30th October 2020) - Tran, Jessica; Huen, Auris; Duvic, Madeleine
Abstract : Patients with mycosis fungoides have an increased risk for additional malignancies, particularly hematologic malignancies. Of the malignancies that have been associated with mycosis fungoides, renal cell carcinoma and other solid tumor malignancies have not been studied extensively. In this case series, we describe three mycosis fungoides patients who were diagnosed with clear cell renal cell carcinoma and discuss the potential pathophysiology underlying this association.